The Current Status in Terms of Vaccination for Individuals Infected with Human Immunodeficiency Virus - Nan Xu; Yanru Shen; Weijin Huang; Jianhui Nie (Viruses)
Human immunodeficiency virus (HIV)-infected individuals have an increased risk of various infections due to their impaired host immune system, resulting in higher morbidity and mortality rates. These patients severely suffered during the COVID-19 epidemic, the influenza epidemic and the spread of monkeypox. Reducing serious infections is one of the most important measures to improve HIV-infected individuals’ quality and length of life. Based on the preparation processes and their antigenic properties, vaccines are divided into several types, including inactivated vaccines, attenuated live vaccines, recombinant protein vaccines, toxoid vaccines, polysaccharide vaccines, polysaccharide (protein) combined vaccines, nucleic acid vaccines, viral vector vaccines, etc. With the innovation of vaccine preparation technology in recent years and the acceleration of vaccine approval and market launch, more and more vaccine products suitable for HIV-infected individuals have become available. Because of their deficient immune systems, the type of vaccines and the schedule of vaccinations available to individuals living with HIV are sometimes different from those with healthy immune systems. This article reviewed the current status of vaccination in and shed light on the vaccination strategies for HIV-infected persons in terms of their safety and effectiveness.